PONAŠANJE POTROŠAČA U SPORTU - Čedomir Ljubojević; Larisa Vetro (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
This paper is primarily interested in sport consumers, and the authors highlight that the success of any sport organisation depends upon successful relations with customer. Undestanding the behavior of sport consumers represents an important fi eld of study. The purpose of this paper is to examine how and why consumers develop, enter into, and maintain relationships in a sports marketing context. Understending the infl uence on customer behavior provides the sport manager with an enhanced indication where to direct marketing efforts. This paper indicates that relationships are among the most important and powerful aspects of sports marketing